Learning Curve of Ex Vivo Liver Resection and Autotransplantation in Treating End-Stage Hepatic Alveolar Echinococcosis: A RA-CUSUM Analysis - Qiu, Yiwen; Yang, Xianwei; Wang, Tao; Shen, Shu; Yang, Yi; Huang, Bin; Wang, Wentao (Frontiers in Surgery, 2021)
Background This retrospective study aimed to evaluate the safety and learning curve of ex vivo liver resection and autotransplantation (ELRA). Methods A total of 102 consecutive end-stage HAE patients who underwent ELRA between 2014 and 2020 in West China Hospital were enrolled. The primary endpoint was major postoperative complications (CCI > 26). The ELRA learning curve was evaluated using risk-adjusted CUSUM (RA-CUSUM) methods. The learning phases were determined based on RA-CUSUM analysis and tested for their association with intra- and postoperative endpoints. Results The median surgery time was 738 (659-818) min, with a median blood loss of 2250 (1600-3000) mL. The overall incidence of major morbidity was 38.24% (39/102). RA-CUSUM analysis demonstrated a learning curve of 53 ELRAs for major postoperative complications. The learning phase showed a significant association with the hemodynamic unstable time (HR -30.29, 95% CI -43.32, -17.25, P<0.0001), reimplantation time (HR -13.92, 95% CI -23.17, -4.67, P=0.004), total postoperative stay (HR -6.87, 95% CI -11.33, -2.41, P=0.0033) and postoperative major morbidity (HR 0.25, 95% CI 0.09, 0.68, p=0.007) when adjusted for age, disease course, liver function, and remote metastasis. Discussion ELRA is feasible and safe with a learning curve of 53 cases for major postoperative complications.